2006
DOI: 10.1038/sj.emboj.7601017
|View full text |Cite
|
Sign up to set email alerts
|

Bex1, a novel interactor of the p75 neurotrophin receptor, links neurotrophin signaling to the cell cycle

Abstract: A screening for intracellular interactors of the p75 neurotrophin receptor (p75NTR) identified brain‐expressed X‐linked 1 (Bex1), a small adaptor‐like protein of unknown function. Bex1 levels oscillated during the cell cycle, and preventing the normal cycling and downregulation of Bex1 in PC12 cells sustained cell proliferation under conditions of growth arrest, and inhibited neuronal differentiation in response to nerve growth factor (NGF). Neuronal differentiation of precursors isolated from the brain subven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 56 publications
1
95
0
Order By: Relevance
“…3). This finding is consistent with the report that Bex1 protein is highly expressed in developing muscle, where it is localized in somatic mesenchyme [14]. We suggest that the lack of Bex1 in mice may alter normal development of muscle and lead to a reduction in exercise performance.…”
Section: Generation Of Bex1 Knock Out Micesupporting
confidence: 93%
See 1 more Smart Citation
“…3). This finding is consistent with the report that Bex1 protein is highly expressed in developing muscle, where it is localized in somatic mesenchyme [14]. We suggest that the lack of Bex1 in mice may alter normal development of muscle and lead to a reduction in exercise performance.…”
Section: Generation Of Bex1 Knock Out Micesupporting
confidence: 93%
“…There are several reasons why a Bex1 and CaM interaction during skeletal muscle regeneration would be important to elucidate. Expression of Bex1 is transiently elevated at the end of the proliferation state of skeletal muscle regeneration [9,10] and several studies implicate the Bex1 protein in cell growth and differentiation [13,14]. On the other hand, CaM is a ubiquitous Ca2+ binding protein, but one that is poorly studied in muscle regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…TrkA and BEX3 co-expressed in embryonic rat dorsal root ganglia (DRG) neurons and also form complex further suggesting a possible role BEX3 in neuron development. Like BEX3, BEX1 was also found to be associated with p75NTR in PC12 cells and the interaction was independent of NGF stimulation [16].…”
Section: Bex Proteins In Neurotrophin Receptor Signalingmentioning
confidence: 95%
“…Furthermore, overexpression of BEX1 in PC12 cells was associated with reduced NFκB activity in response to NGF as well as elevated differentiation capacity, while knockdown of BEX1 potentiated NFκB activity in response to NGF [16]. Therefore, it has been suggested that both BEX1 and BEX3 interact with p75NTR and regulate NGF-induced apoptosis and differentiation in neural tissues through NF-B (Fig.…”
Section: Bex Proteins In Neurotrophin Receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation